The Male Tomcat Fighter as Superior Cadres for Handling Paederus Dermatitis at Daarul Qur'an Islamic Boarding School, Karanganyar, Central Java - Lathif, Muh Nazir (Journal Intellectual Sufism Research (JISR), 2019)
Dermatitis venenata caused by Paederin poison called Paederus Dermatitis. This type of dermatitis causes inflammation of the skin with distinctive characteristics such as erythema and pruritus accompanied by vesicles in the cervical region. This type of inflammation generally occurs in high temperature areas with tropical climates. Indonesians generally do not understand the incidence of dermatitis, so the incidence of dermatitis is still high and has not been treated appropriately. Daarul Quran Putra Islamic Boarding School has high incidence in paederus dermatitis so that cadres are formed called Tomcat Fighter as Detective Tomcat to control and overcome the incidence of Paederus Dermatitis. This service aims to determine the success of the Fight Tomcat strategy at the Daarul Qur'an Islamic Boarding School in Karanganyar, Central Java. 10 male students given the treatment of education. In the data there was an increase in recovery from 82 sufferers becoming fully recovered. The conclusion is the education we gave to male cadres proves the success of Fight Tomcat strategy to recover the suffered students.